ANALYSIS THE USE OF PLURAL NOUNS IN “SELECT READINGS’ BY LINDA LEE AND ERIK GUNDERSEN - Aulia Putri Senjani (Faculty of Education and Teachers Training, 2021)
This research aims to search into one of the most commonly found forms of a plural noun in the book